Characterization of Peptostreptococcus species by aminopeptidase profiles and genotyping methods. - Ng, James. (University of Ottawa (Canada), 1996)
Peptostreptococcus species are anaerobic Gram-positive cocci associated with a variety of female genital tract infections that includes bacterial vaginosis and pelvic inflammatory disease. One of the accepted indicators in bacterial vaginosis is the production of proteases which involves Peptostreptococcus spp. One hundred Peptostreptococcus isolates were screened for aminopeptidase activities and for proteolytic activity. Five ATCC Peptostreptococcus strains and 95 clinical isolates comprising P. anaerobius, P. asaccharolyticus, P. magnus, P. micros, and P. prevotii were included. Statistical analysis showed that the prevalence of gelatin hydrolysis is significantly correlated to the number of positive aminopeptidase reactions to synthetic peptides among the 5 Peptostreptococcus species. The rapid ID32A kit was also used to identify the 100 Peptostreptococcus isolates as compared to conventional biochemical tests and gas-liquid chromatography, the current "gold" standard method. Overall, the rapid ID32A kit is a useful method for the rapid differentiation of P. anaerobius and P. asaccharolyticus from other Peptostreptococcus spp. Alternate methods should be used to speciate isolates of P. magnus, P. micros, and P. prevotii. Protein L (L) and albumin-binding (A) proteins have been identified as putative virulence factors of P. magnus isolates. When 32 P. magnus isolates from 4 different countries were screened for protein L gene sequences, the only positive isolates were three which had been previously identified. In order to determine whether these putative virulence factors might be clonal, protein L-containing (L$\sp+$ A$\sp-$) or albumin-binding isolates (L$\sp-$ A$\sp+$) and unrelated isolates (L$\sp-$ A$\sp-$) were analyzed using three genotyping methods. Based on patterns from PFGE and ribotyping, cluster analysis showed that the three L$\sp+$A$\sp-$ isolates were more closely related to each other than with other isolates. Six of eight L$\sp-$A$\sp+$ isolates formed two indistinguishable groups of three isolates each, but these two groups were genetically distant from the other two related L$\sp-$A$\sp+$ isolates. L$\sp-$A$\sp-$ isolates were not related, either among themselves, or to any other isolates. Thus, L$\sp+$ and A$\sp+$ phenotypes and genotyping methods (PFGE and ribotyping) are useful for differentiating P. magnus isolates and identifying specific strain types. In conclusion my studies have found that the proteolytic activity of Peptostreptococcus spp. is actually due in part to an array of aminopeptidase reactions. As well, certain isolates of Peptostreptococcus species require further taxonomic work which will likely lead to changes in classification and nomenclature. All 11 clinical isolates originally identified as P. prevotii by the "gold" standard methodology were other identified as P. magnus (n = 4) or could not be identified by the rapid ID32A kit. Protein L-containing and some albumin-binding P. magnus isolates are clonal in structure. This is in agreement with past studies that most pathogenic isolates of bacteria are descendent from one parental strain. (Abstract shortened by UMI.)
Keywords: Biology, Microbiology.